Reuse of rainwater through the construction of cisterns - Oliveira, Paulo Giovani Saraiva de; Pereira, Mauricio de Sousa (Seven Editora, 2023)
Water is an essential natural resource for life on the planet, either as a biochemical component or as a living thing, as a means of life for various plant and animal species, as a representative element of social and cultural values, and even as a factor of production of various final and intermediate consumer goods. However, the increasing population has increased the demand for this good. On the other hand, the supply of drinking water becomes increasingly scarce to meet the diverse needs of the population. Given this scenario, it is essential to implement methodologies that enhance the rational use of water.  Water resources come from various natural origins, such as aquifers, groundwater, and rivers essentially for the existence of all living beings, which is the essential reason why society is increasingly concerned with the availability of drinking water on our planet. Therefore, it is necessary to study the ways of reusing rainwater as a way of saving and preserving drinking water. In the present work, d e research was carried out a study on the feasibility of the use of rainwater throughout the country, taking into account the differences in precipitation. Thus, for this purpose, it was necessary to identify the rainfall regime of the different Brazilian capitals through the database of the National Institute of Meteorology (INMET), determine the volumes of rainwater reservoirs for each situation, and evaluate the influence of the rainfall regime on the potential for rainwater use. DOI:https://doi.org/10.56238/devopinterscie-251